CMOS VLSI subsystems for low-voltage low-power applications - Kong, Zhi Hui (2008)
Low-voltage and low-power circuit design has become vitally indispensable with the emergence and increasing popularity of off-the-shelf handheld electronic devices. Indeed, portable appliances are stimulating and dominating the System-on-a-Chip (SoC) mass consumer market at a tremendously high pace. As a result, it is essential to continue venturing into higher-end approaches and realizing more refined solutions to achieve further low-voltage/low-power design while sustaining high-speed performance and small-area consumption. In this dissertation, we present several innovative CMOS VLSI subsystem designs for use in low-voltage low-power environments.